1987
DOI: 10.1159/000184489
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial IgA Nephropathy and Idiopathic Nephrotic Syndrome

Abstract: A 17-year-old male presented with nephrotic syndrome associated with microscopic hematuria. Renal biopsy showed only minor glomerular abnormalities (light microscopy). Immunohistology demonstrated strong mesangial deposition of IgA. Electronmicroscopy disclosed widespread effacement of foot processes in combination with isolated osmiophilic mesangial deposits. The patient responded to standard corticosteroid therapy with complete disappearance of proteinuria. Microscopic hematuria, however, persisted. Five mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
4
4
1
Order By: Relevance
“…We have recently shown that the increase in salivary IgAl and neopterin was not specific for IgA GN but was also observed in MGN and INS, suggesting an activation of the lymphoid system at the mucosal site in these nephrop athies, too [19]; an increase in total IgA in nasal washings of patients with glomerulopathies other than IgA GN was also reported by Yagame [25]. Furthermore, the find ing in INS of an increase in both IgAl and IgA2 at mucosal sites [19], and the detection in our study of high serum levels of specific IgA to environmental antigens strengthen the hypothesis that steroid-responsive ne phrotic syndrome with concomitant IgA deposits should not be considered as a distinct syndrome but rather a minimal-change disease with nonspecific mesangial trapping of IgA [26][27][28][29][30], A similar mechanism might be considered in MGN associated with IgA deposits [31].…”
Section: Discussionsupporting
confidence: 90%
“…We have recently shown that the increase in salivary IgAl and neopterin was not specific for IgA GN but was also observed in MGN and INS, suggesting an activation of the lymphoid system at the mucosal site in these nephrop athies, too [19]; an increase in total IgA in nasal washings of patients with glomerulopathies other than IgA GN was also reported by Yagame [25]. Furthermore, the find ing in INS of an increase in both IgAl and IgA2 at mucosal sites [19], and the detection in our study of high serum levels of specific IgA to environmental antigens strengthen the hypothesis that steroid-responsive ne phrotic syndrome with concomitant IgA deposits should not be considered as a distinct syndrome but rather a minimal-change disease with nonspecific mesangial trapping of IgA [26][27][28][29][30], A similar mechanism might be considered in MGN associated with IgA deposits [31].…”
Section: Discussionsupporting
confidence: 90%
“…The single pathologic finding that correlated with the presentation of full NS was extensive (median=90%) foot process effacement. The clinical and biopsy findings in these 17 patients, as well as similar cases that have been previously reported (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), are most consistent with mild IgAN with superimposed MCD.…”
Section: Discussionsupporting
confidence: 84%
“…Many of the patients are rapidly responsive to treatment with corticosteroids. Such cases are uncommon but have been presented as case reports and in small series over the last 30 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some of these reports have suggested that the clinical and pathologic findings in these unusual cases of IgAN (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), as well as the clinical outcomes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), are more typical of mild IgAN with superimposed MCD.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently read with great interest the paper by Rambausek et al [1], During the period from 1981 to 1985, IgA nephropathy was diagnosed in 63 patients who ac count for 14.6% of all biopsy-confirmed cases with pri mary glomerular disease in our hospital. Nephrotic syn drome was present in 8 patients (12.7%).…”
Section: Iga Nephropathy and Nephrotic Syndrome1mentioning
confidence: 99%